Deep vein thrombosis. Issue 6 (June 2020) - Allen, Lisa; Wilkinson, Andrew
Deep vein thrombosis (DVT) is a common and serious condition with a substantial risk of morbidity and mortality for patients. A diagnosis of DVT affects both the physical health and psychosocial functioning of patients. It represents a significant cost to the NHS in both expenditure and resource allocation. Management should focus on early recognition, prompt referral and prevention of its associated complications. This article aims to provide relevant background knowledge about DVT with advice on assessment using a clinical risk tool and appropriate referral to secondary care.